Expression Profiles of lncRNAs and mRNAs in the Mouse Brain Infected with Pseudorabies Virus: A Bioinformatic Analysis - Yanwei Li; Teng Tu; Yan Luo; Xueping Yao; Zexiao Yang; Yin Wang (Viruses)
Pseudorabies virus (PRV) is a pathogen that causes severe neurological dysfunction in the host, leading to extensive neuronal damage and inflammation. Despite extensive research on the neuropathogenesis of α-herpesvirus infections, many scientific questions remain unresolved, such as the largely unknown functions of long non-coding RNAs (lncRNAs) in herpesvirus-infected nervous systems. To address these questions, we used RNA sequencing (RNA-seq) to investigate the expression profiles of lncRNAs and mRNAs in the brains of mice infected with PRV. Through bioinformatic analysis, we identified 316 differentially expressed lncRNAs and 886 differentially expressed mRNAs. We predicted the biological functions of these differentially expressed lncRNAs and mRNAs using the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases, and the results showed that the differentially expressed transcripts were mainly involved in the innate immune response. Finally, we validated the differential expression trends of lncRNAs and mRNAs using quantitative real-time PCR (q-PCR), which were consistent with the sequencing data. To our knowledge, this is the first report analyzing the lncRNA expression profile in the central nervous system (CNS) of mice infected with PRV. Our findings provide new insights into the roles of lncRNAs and mRNAs during PRV infection of the host CNS.